Halal Drug Supervision from the Perspective of Maqasid Syari'ah and Law No. 17 of 2023 on Health - Fitri Rafianti; T. Riza Zarzani; Arif Sahlepi (Journal of Research in Social Science and Humanities, 2025)
The issue of drug halal certification has become a crucial concern for Muslims, especially given the vital nature of drugs for the preservation of life (hifz an-nafs), which is one of the main objectives of Sharia law (Maqasid Syari'ah). The majority of drugs on the market still use raw materials or production processes whose halal status is questionable, such as the use of pork gelatin or alcohol. The government has responded to this challenge by issuing regulations, including Law No. 33 of 2014 on Halal Product Guarantee (JPH) and, most recently, Law No. 17 of 2023 on Health. Law No. 17 of 2023 brings significant changes, containing provisions related to the supervision of medicines and pharmaceutical preparations. However, the emergence of various problems in the implementation of halal certification for drugs—including the testing process, the availability of alternative halal raw materials, and the urgency of drug availability for emergency conditions—requires in-depth analysis. This study aims to examine how the harmonization and implementation of halal drug requirements can be effectively realized without compromising the guarantee of drug availability and accessibility for the public, as mandated by the Health Law. This study formulates two main issues: (1) How can the issue of the halal status of medicines in circulation be analyzed and resolved within the framework of the five basic objectives of Maqasid Syari'ah, particularly in terms of protecting life (hifz an-nafs); and (2) How the synchronization, implementation, and urgency of halal drug procurement are regulated and guaranteed based on the provisions of Law No. 17 of 2023 concerning Health, as well as the legal challenges that arise in its implementation. This study uses a normative legal method with a conceptual approach and a statute approach. Primary data sources include Law No. 17 of 2023 concerning Health and Law No. 33 of 2014 concerning JPH, as well as various related implementing regulations. The results of the study show that the obligation of halal certification for medicines is in line with the principle of protection of life (hifz an-nafs) in Maqasid Syari'ah, which guarantees the safety and spiritual confidence of users. The issue of halal often centers on raw materials that come from unclean or haram sources, but from the perspective of Maqasid Syari'ah, exceptions (rukhsah) can be granted for drugs sourced from non-halal ingredients if there are no halal alternatives (darurat syar'iyyah), as long as it is necessary to save lives, in line with the fiqh rule on the priority of preserving life. Law No. 17 of 2023 strengthens the role of the state in ensuring the availability of quality medicines and health services, including safety and halal aspects through an integrated monitoring mechanism, although the main focus is on safety and clinical benefits. The biggest challenge in implementation is creating an integrated and rapid halal pharmaceutical raw material supply system, as well as ensuring that the certification process does not become an obstacle to the availability of essential medicines. Therefore, regulatory harmonization and incentive policies are needed to encourage the pharmaceutical industry to switch to halal raw materials without disrupting market stability and public access to needed medicines